Socially significant diseases affecting the health of the youth of the Republic of Kazakhstan (Based on official statistics and Social Research) (Journal of actual problems of jurisprudence, 2018)
In the scientific article reflected the official statistics and the results of sociological research on socially significant diseases affecting the health of young people in the Republic of Kazakhstan. The authors show the dynamics of social diseases and diseases that pose a danger to others (tuberculosis, AIDS, cancer, diabetes, mental disorders) among the youth of the Republic of Kazakhstan.Key words: socially significant diseases, epidemiological situation, health care, AIDS, malignant neoplasms.